KEANEKARAGAMAN HAMA PADA TANAMAN MELON (Cucumis melo L.) - Sumeinika Fitria Lizmah; Resti Yusniar Gea (Jurnal Agrotek Lestari, 2018)
The production of melon was decline due to decreased production area and also pest and disease offence. The pest attacks occur in the vegetative and generative phase, but the most damaging and detrimental are in generative phase. This study aims to determine the diversity of insects on melon plants. The study was conducted in September 2018 in experimental gardens and laboratory of Agriculture Faculty, Teuku Umar University. The results of the study obtained the abundance of insects in melon plants amounted to 374 individu, which consists of 38 spesies. Insects are found to have different character, there are as pest, parasitoid, and predator. The fruit flies (Tephritidae) is the dominant of pest that attack melon in generative phase. Diversity of Shannon-Wienner indeks shows 0.820, that mean the diversity in melon plant in generative phase was lowly. Key word: diversity, fruit flies, insects, melon